2016
DOI: 10.11114/afa.v2i2.1591
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Audit Committee Independence in the Financial Sector of Bangladesh

Abstract: This paper examines the determining factors of the audit committee independence in the financial sector of Bangladesh by employing a cross-sectional regression analysis on 72 financial firms. The paper reveals that firms with large boards and more non-executive directors tend to provide more independence to the auditors. Also, large firms with potential growth opportunities show less interest in giving freedom to the audit committee members; whereas firms with the higher leverage demand more audit committee in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…Based on research conducted by Al-Janadi et al, (2013) there was no significant relationship between the proportions of the independent audit committee with voluntary disclosure. In another study, it was mentioned that an increase in the members of the independent audit committee does not mean that the more experienced audit committee members become increased as well (Adhikary & Mitra, 2016).…”
Section: Independent Audit Committee and Voluntary Disclosurementioning
confidence: 99%
“…Based on research conducted by Al-Janadi et al, (2013) there was no significant relationship between the proportions of the independent audit committee with voluntary disclosure. In another study, it was mentioned that an increase in the members of the independent audit committee does not mean that the more experienced audit committee members become increased as well (Adhikary & Mitra, 2016).…”
Section: Independent Audit Committee and Voluntary Disclosurementioning
confidence: 99%
“…In addition, both Collier (1993) and Beasley and Salterio (2001) reported that keeping pace with the increase in board size, the ability of a firm to employ more independent directors increase. Moreover, Adhikary and Mitra (2016) found that firms with larger board had more independent audit committee. On the other hand, it is also argued that monitoring role is stronger in a smaller board and it is less probable that the board be captured by the CEO when it is small.…”
Section: Board Sizementioning
confidence: 99%
“…This study recognizes profitability as having an important link with board independence. Adhikary and Mitra (2016) hypothesized that when there is a possibility of private gain for insiders, firms should employ more independent directors in audit committee. From that hypothesis, it is reasonable to conclude that insiders have incentives to manipulate firm profitability to serve self-interests.…”
Section: Profitabilitymentioning
confidence: 99%
“…Contrary to the advanced systems of corporate governance in developed economies, typically in Bangladesh, ownership is concentrated and consequently boards are influenced/dominated by the owners having significant stakes of shares. Moreover, the firms have one-tiered boards where both executive and nonexecutive directors work collectively in one organizational layer (Rashid, De Zoysa, Lodh, & Rudkin, 2012;Rashid, 2018) where the proportion of executive directors is higher (Adhikary & Mitra, 2016). Given the above circumstances along with an existence of an inefficient market, less takeover regulations, and takeover processing costs, the boards have discretion and power to influence their remuneration irrespective of firms` financial performance.…”
Section: The Context Of Bangladeshmentioning
confidence: 99%